THE ROLE OF TOLL-LIKE RECEPTORS POLYMORPHISM IN ATHEROSCLEROSIS COMPLICATIONS DEVELOPMENT - O. L. Barbarash; A. S. Golovkin; A. V. Ponasenko; A. G. Kutikhin; I. I. Zhidkova; M. V. Khutornaya; R. R. Salakhov; L. S. Barbarash (Российский кардиологический журнал)
Aim. To reveal the association of polymorphic types of Toll-like receptor genes with myocardial infarction (MI), stroke in patients with coronary heart disease (CHD).Material and methods. Totally 292 patients studied, with CHD and anamnesis of stroke and/or MI. The association of 8 polymorphic loci of 4 genes were studied: TLR1 (rs5743551 & rs5743611), TLR2 (rs3804099 & rs5743708), TLR4 (rs4986790 & rs4986791), TLR6 (rs3775073 & rs5743810).Results. The association of allele C of polymorphism rs5743551 gene TLR1 is associated with higher risk of earlier CHD onset (younger than 55 y.o.). Heterozygous (A/G) genotype of polymorphism rs5743810 TLR6 is protective against the risk of earlier CHD onset (younger than 55 y.o.). Heterozygous (C/T) genotype of polymorphism rs5743551 gene TLR1 is associated with higher risk of stroke in CHD patients. The associations revealed with age, gender and cardiovascular complications by polymorphisms of TLR genes: males, having CHD, homozygous by minor allele (С/С) of polymorphism rs3804099 gene TLR2, have reduced risk of of MI development not related to age; heterozygous (C/T) genotype of polymorphism rs5743551 of gene TLR1 is associated with the increased risk of stroke in CHD patients older than 55 y.o. not depending on gender; heterozygous (T/C) genotype of polymorphism rs3775073 gene TLR6 is associated with increased risk of MI in younger than 55 y.o. patients with CHD not related to gender.Conclusion. Some associations of polymorphic Toll-like receptors genes with the development of atherosclerosis complications (MI, stroke) in CHD are revealed.